PENGARUH KOMPETENSI APARATUR, KOMITMEN ORGANISASI, DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN DANA DESA (Studi Empiris pada Desa-Desa di Kabupaten Bintan) - Larastika Medianti; Taufeni Taufik; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to know the influence of apparatus competence, organizational commitment, and communityparticipation on village fund management in the northern bintan subdistrict, the kijang mountains, the lobam kuala series, bintan bay, bay sebong, and toapaya, bintan district. The population used in this study were 19 villages in bintan district. The Samples in this study were village head, the village secretary, the village treasurer (head of financial affairs), and head of affairs. Data collection in this research is using purposive sampling, where total respondents in this research is 95 peoples. Data analysis was done with multiple linier regression model with SPSS software 21.0 version. The results obtained that the competence of rural apparatus, commitment of village government organizations, and community paticipation have a significat effect on village fund management.Keywords : Management of Village Funds, Competence Apparatus, Organizational Commitment, and Society Participation